Assessment of Family planning services utilization among women of Union Council Bangoin (Rawalakot) Azad Jammu and Kashmir - Mehwish Fayaz; Qandeel Tahir; Tehmina Zafar; Muhammad Usman Tayyab Butt (Journal of Bahria University Medical and Dental College, 2023)
Objectives: To determine the percentage of women in Union Council Bangoin (Rawalakot) Azad Jammu and Kashmir who use family planning services, and to determine the relationship between demographic characteristics and family planning service use (AJ&K). Study design and setting: A cross-sectional study was conducted in UC Bangoin (Rawalakot) Azad Jammu and Kashmir over the duration of 6 months, from 5 January to 5 July 2021. Methodology: A sample of 344 married women with the age range 18 to 45 was obtained. The study's assessment instrument was developed from an existing assessment tool (Reproductive health knowledge and services utilization among rural adolescence in Ethiopia 2014). It included 14 questions on demographics and 13 questions about the use of family planning services. Results: High utilization was 52% (n=179) while low utilization was 48% (n=165). Most of them had fear of side effects of using contraception (n=170, 48.9%). Chi-square test showed significant association (p-val =0.05) between fear of side effects of using contraception, decision of using contraception, education level, distance from home to hospital, number of children, exposure to mass media and utilization of family planning services. Conclusion: There was low family planning services utilization in that area. Study showed that there was a strong association between fear of side effects of using contraception, low education and low exposure to mass media with utilization of family planning services in Union Council Bangoin (Rawalakot) Azad Jammu and Kashmir (AJ&K).